Hospital Sterilization Room Door Interlock System Prototype Using Electric Contactors - Ardiansyah, Suhir; Fachri, Muhammad Rizal; Fathiah, Fathiah (PTE FTK UIN Ar-Raniry, 2025)
Controlling access to sterile hospital rooms can be effectively managed using a secure and reliable interlock system based on electrical contactors, which ensures that only one door is open at a time to prevent cross-contamination. This study aims to design and test a prototype of an interlock system for sterile room doors using an electrical contactor as the main controller. The research follows stages of design, testing, and performance evaluation. The system utilizes solenoid door locks controlled by contactors to automate door locking and opening. Testing focuses on measuring the output current of the contactors and the solenoid’s response time during door operations. Results show that contactor 1 outputs 7.63 mA, and contactor 2 outputs 7.64 mA. Solenoid door lock 1 has an average operating time of 0.80 seconds with a delay of 0.89 seconds, while solenoid 2 operates at 0.96 seconds with a 0.97-second delay. The system demonstrates stable performance and complies with sterile room safety standards. It is suitable for hospital implementation and can be further enhanced with remote monitoring and automatic alarm features to improve operational supervision